Blocking effect of methylflavonolamine on human NaV1.5 channels expressed in Xenopus laevis oocytes and on sodium currents in rabbit ventricular myocytes - Fan Xin-rong; Ma Ji-hua; Zhang Pei-hua; Xing Jun-lian (Acta Pharmacologica Sinica; Vol 31, No 3 (March 2010): Acta Pharmacologica Sinica, 2016)
Aim: To investigate the blocking effects of methylflavonolamine (MFA) on human NaV1.5 channels expressed in Xenopus laevis oocytes and on sodium currents (INa) in rabbit ventricular myocytes. Methods: Human NaV1.5 channels were expressed in Xenopus oocytes and studied using the two-electrode voltage-clamp technique. INa and action potentials in rabbit ventricular myocytes were studied using the whole-cell recording. Results: MFA and lidocaine inhibited human NaV1.5 channels expressed in Xenopus oocytes in a positive rate-dependent and concentration-dependent manner, with IC50 values of 72.61 μmol/L and 145.62 μmol/L, respectively. Both of them markedly shifted the steady-state activation curve of INatoward more positive potentials, shifted the steady-state inactivation curve of INatoward more negative potentials and postponed the recovery of the INa inactivation state. In rabbit ventricular myocytes, MFA inhibited INawith a shift in the steady-state inactivation curve toward more negative potentials, thereby postponing the recovery of the INa inactivation state. This shift was in a positive rate-dependent manner. Under current-clamp mode, MAF significantly decreased action potential amplitude (APA) and maximal depolarization velocity (Vmax) and shortened action potential duration (APD), but did not alter the resting membrane potential (RMP). The demonstrated that the kinetics of sodium channel blockage by MFA resemble those of class I antiarrhythmic agents such as lidocaine. Conclusion: MFA protects the heart against arrhythmias by its blocking effect on sodium channels.